IMPLEMENTASI METODE PQRST DALAM UPAYA MENINGKATKAN KETERAMPILAN MEMBACA (READING) MAHASISWA - Johan Sinulingga (BAHAS, 2011)
Generally, this research is aimed at improving students’ reading comprehension by implementing the PQRST teaching method. Subjects of the research are the students of 2009/2010 academic year taking reading I subject. The research uses classroom action research method. The data are collected by reading comprehension test for measuring the students’s reading comprehension and questionarrie with Liket scale for collecting the students’ perceptions toward  PQRST teaching method. The data are analyzed by descriptive technique. The results of research show that 1) the preliminary comprehension of the students’ reading comprehension is relative poor and very poor in which the distribution of comprehension is not proportional, 2) After first cycle, the students’ reading comprehension improve relativel significantly, 3) Then, after the end of the research, the students’ reading comprehensions improve significantly which most of them (52,94) obtains grade B or  it is categorized good and (8,82%) reaches grade A. Only about (32.35%) and (2,94%) of them still have grade C and D. However, nobody gets failed.  In term of perception, generally the students have positive and good responds and perception toward the PQRST teaching method for teaching and learning reading comprehension subject.   Kata Kunci : metode PQRST, keterampilan membaca